Upcycling of groundwater treatment sludge to an erdite nanorod as a highly effienct activation agent of peroxymonosulfate for wastewater treatment. (August 2020) - Zhu, Suiyi; Song, Xiang; Chen, Yu; Dong, Ge; Sun, Tong; Yu, Hongbin; Yu, Yang; Xie, Xinfeng; Huo, Mingxin
Abstract: Groundwater treatment sludge is an Fe-rich waste continuously generated in large amounts through potable water production at groundwater treatment plants. In this study, the sludge was converted to erdite nanorod particles via a one-step hydrothermal route with only adding Na2 S. The sludge was a mixture of ferrihydrite, hematite and Si/Al oxides. After hyddrothemal treatment, erdite was primarily formed from ferrihydrite, which accounted for 91.2% of the Fe species in the sludge, whereas approximately 8.8% of hematite accounted for the Fe species that remained before and after the reaction. The produced erdite nanorods were approximately 200 nm in diameter and 1–3 μm in length. They also exhibited a superior efficiency in peroxymonosulfate (PMS) activation. Nearly 100% quinoline removal (initail concentration = 10 mg L −1 ) was achieved when the eridite nanorods were used with PMS. The removal rate of quinoline was much higher than that of raw sludge, nano-scale zero-valent iron, FeS, hematite and magnetite. The erdite nanorods or the PMS alone had a quinoline removal rate of less than 20%. The erdite nanorods were spontaneously hydrolysed to generate Fe 2+ for PMS activation and to form S species for the reductive cycling of Fe 3+ to Fe 2+, which likely promoted PMS activation. This study not only highlighted a facile method to recycle the sludge for erdite nanorod preparation but also presented a novel nanomaterial that could efficiently activate PMS for organic wastewater treatment. Highlights: Only ferrihydrite not hematite was transformed to erdite nanorod. Erdite was a superior activator of peroxymonosulfate (PMS). Hydrolysed S species of erdite promoted the reductive recycling of Fe 3+ to Fe 2+ . S and Fe in erdite had synergistic effect for PMS activation.